Investigating the effect of nanoclay on the mechanical properties of asphalt cold recycling using bitumen emulsions - Seyed Sadegh Naseralavi; Mohammad Reza Nozari Gilan (مدل‌سازی پیشرفته در مهندسی عمران, 2024)
To investigate the effect of nano-clay on the fatigue properties of cold recycled asphalt mixtures and explore its potential to enhance the mechanical performance of these materials. The study involved adding nano-clay to cold recycled asphalt mixtures in varying proportions. A four-point bending test was employed to evaluate the fatigue properties and assess the impact of different nano-clay percentages on the performance of the mixtures.The addition of nano-clay significantly enhanced the fatigue properties of cold recycled asphalt mixtures when used in appropriate amounts. However, percentages exceeding one percent led to a reduction in fatigue resistance, highlighting the importance of optimizing additive proportions. Nano-clay is a promising additive for improving the mechanical properties of cold recycled asphalt mixtures, particularly fatigue resistance. However, precise control over the additive quantity is crucial, as excessive amounts may adversely affect performance. These findings provide valuable insights for optimizing cold recycling processes and guiding future research.